PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA DI DESA BRANG KOLONG KECAMATAN PLAMPANG KABUPATEN SUMBAWA - Novi Kadewi Sumbawati; S Syafruddin; Nasrul Gunawan (Pusat Riset dan Publikasi, 2021)
This study aims to determine: The level of community participation in development in Brang Kolong Village, Plampang District, Sumbawa Regency. Participation of the community in all development activities starting from planning, decision making, implementation, evaluation, and utilization of results. The problem in this research is how the community participation in the process of planning, implementing, and maintaining village development in Brang Kolong Village. The purpose of this study was to determine how community participation in the process of planning, implementing, and maintaining village development in Brang Kolong Village. This research was conducted in a qualitative descriptive manner and the methods used were observation, interview, documentation, and data analysis methods. The author took informant data using purposive sampling, which was 15 people. The results of this study indicate that community participation in the village development process in Brang Kolong Village, there are several stages of development, namely: (1) Planning (2) Decision Making (3) Implementation (4) Evaluation, and (5) Utilization of Development Results.